Rébellions post-féministes - Jules Sandeau (Genre, Sexualité et Société)
This article examines the representations of gender in young adult dystopian science fiction movies post Hunger Games (2012). In order to avoid what is often a blind spot in studies on these contemporary Hollywood productions, I will articulate my analysis of gender roles in these films with an analysis of the gender relations which shape these roles. This will allow me to shed light on different shortcomings of these films that are symptomatic of a contemporary imaginary that is dominated, in relation to gender issues, by a paradigm that has traditionally been called “post-feminism”.